2013
DOI: 10.1016/j.ecoenv.2013.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological responses of the root system of Indian mustard (Brassica juncea L. Czern.) and rapeseed (Brassica napus L.) to copper stress

Abstract: Copper (Cu) is an essential microelement for growth and development, but in excess it can cause toxicity in plants. In this comparative study, the uptake and accumulation of Cu as well as the morphological and physiological responses of Indian mustard (Brassica juncea L. Czern.) and rapeseed (Brassica napus L.) roots to Cu treatment were investigated. The possible involvement of redox active molecules (reactive oxygen species and nitric oxide) and modification in cell wall structure associated with Cu-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 59 publications
15
68
0
Order By: Relevance
“…Previous studies have shown that elongations of roots in plants are affected by the redox status in their apical region (Córdoba-Pedregosa et al 2005). Changes in the redox status contribute to cell wall secondary thickening resulting in the reduction of cell growth and are negatively correlated with root elongation (Feigl et al 2013). In this study, for the first time, we observed callose deposition as a result of CuO NPs exposure in roots of B. napus seedlings.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Previous studies have shown that elongations of roots in plants are affected by the redox status in their apical region (Córdoba-Pedregosa et al 2005). Changes in the redox status contribute to cell wall secondary thickening resulting in the reduction of cell growth and are negatively correlated with root elongation (Feigl et al 2013). In this study, for the first time, we observed callose deposition as a result of CuO NPs exposure in roots of B. napus seedlings.…”
Section: Discussionsupporting
confidence: 52%
“…Treatment with PI indicated cytotoxicity, in the root tips of B. napus seedlings treated with CuO NPs. As reported earlier as in the case of excess Cu (Feigl et al 2013), the enhanced ROS generation as a result of the increased Cu levels under CuO NPs treatment caused the cytotoxicity in roots of B. napus seedlings.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations